Innovations in the Context of the Risk Caused by the Covid-19 Pandemic: A Literature Analysis - Kamil DECYK (Communications of International Proceedings, 2024)
The purpose of the considerations presented in the study was to identify innovations introduced during the Covid-19 pandemic. The implementation of the presented assumption was carried out using the method of deductive explanation and a review of international literature. During the literature analysis, it was noticed that the risks resulting from Covid-19, apart from negative effects, were a source of positive phenomena, especially in the case of the industry responsible for new information and communication services. Moreover, the beneficiary of the benefits was naturally the pharmaceutical and medical industries, where the crisis had an unequivocally positive impact. Some entities from the manufacturing industries have diversified their product portfolios, introducing product innovations and thus limiting the risk of interrupting supply chains or the risk of recession. The changes introduced during the pandemic were dominated by business process innovation solutions. The study may constitute the basis for conducting comparative analyzes regarding the intensity of innovative activities in the post-pandemic period and during Covid-19. The work and its results additionally have educational and implicational value. They draw attention to the fact that innovative activity and the implementation of a wide range of innovative solutions not only in business is a sin qua non condition for maintaining or improving the quality of life, but also from the market point of view. The development of innovativeness ensures the survival and development of economic entities, especially in times of crisis and recession, which is directly related to numerous risks, as well as their management.
Keywords: Covid-19 pandemic; innovation; innovative activities; qauality of life; risk management